A recyclable nanosheet of Mo/N-doped TiO2 nanorods decorated on carbon nanofibers for organic pollutants degradation under simulated sunlight irradiation. (January 2019) - Qiu, Jinli; Liu, Fuqiang; Yue, Cailiang; Ling, Chen; Li, Aimin
Abstract: A novel nanosheet of Mo/N-codoped TiO2 nanorods immobilized on carbon nanofibers (MNTC nanosheet) was self-synthesized through two facile steps. The Mo/N-doped TiO2 nanorods dispersed through in situ growth on the network constructed by long and vertical carbon nanofibers (CNFs). The fabricated MNTC nanosheet displayed superb photocatalytic activity of methylene blue (MB), and the degradation ratio by the MNTC nanosheet was nearly twice than that of pure nanoparticles. The photocatalytic activities during the degradation process in the presence of environmental media such as inorganic salts and natural organic matter (NOM) were also determined. Intermediates were analyzed by ion chromatography and electrospray ionization-mass spectrometry to unravel the potential degradation pathways, and the excellent mineralization ratio for MB over MNTC nanosheet was 79.8%. The trapping active species experiments verified that h + was the main active species in the degradation process. Notably, the recycling experiment proved that the MNTC nanosheet was more stable, and it was successfully applied in purifying practical wastewater. Lastly, the fabricated MNTC nanosheet also displayed remarkable degradation performance towards sulfamethoxazole and bisphenol A. Graphical abstract: Highlights: Recyclable MNTC nanosheet photocatalysts were fabricated. The mineralization ratio for MB by the MNTC nanosheet is much higher than that by TiO2 . Environmental media such as inorganic salts and NOM were evaluated. The possible degradation pathways and mechanism were proposed. The practical application of the MNTC nanosheet indicates the potential in the future.